Female genital mutilation/cutting incidence, diagnostic capacities, and obstetric outcomes among migrant women: a single-center retrospective analysis in a 10-year birth cohort in Austria - N. Taumberger; T. Gruber; K. Edler; G. Trutnovsky; T. Bracic; N. Semrl; A.-M. Schütz; K. Eisnecker; K. Tamussino; H. Fluhr (BMC Public Health, 2023)
Abstract Introduction Practical experience in the care of women with female genital mutilation/cutting (FGM/C) is uncommon in Austria. However, affected women require specialized gynecological and obstetric care. In our region, there is currently neither an official counseling center nor specially trained medical personnel to address the special needs of women after FGM/C. The aim of this study was to determine the potential need for obstetric care for women who have undergone FGM/C in our region. Methods We retrospectively reviewed women presenting for delivery at the LKH University Hospital Graz from 1.1.2010 until 31.12.2020 regarding the place of birth and/or the nationality of the mother to filter out women from a country with known FGM/C prevalence according to the UNICEF Global Database. Data on the documentation of FGM/C as well as demographic maternal data and peripartal parameters were gathered. Periods before and after the European refugee crisis in 2015 were compared. Results During the study period, a total of 35,628 deliveries took place at our hospital. 856 (2.4%) deliveries of 539 women were included due to nationality or birthplace in a country with known FGM/C prevalence. We found only 17/539 (3.2%) documented FGM/C cases. The estimated FGM/C prevalence among those patients was, however, 208/539 (38,6%). Women affected by FGM/C in our collective were most frequently from Nigeria, Egypt, Iraq, Ghana, and Somalia. No statistically significant increase in deliveries during the study period in the overall study cohort was observed, with the exception of deliveries of Somali women (p = 0.000). Discussion The discrepancy between documented and expected FGM/C rates (3,2% vs. 38,6%) in our collective suggests that most cases of FGM/C go undetected among women delivering in Austria. These data show the great need for special training for obstetricians and targeted contact points for affected women.